2001
DOI: 10.1083/jcb.200107069
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of class I and class III phosphatidylinositol 3-kinases in phagosome formation and maturation

Abstract: Phagosomes acquire their microbicidal properties by fusion with lysosomes. Products of phosphatidylinositol 3-kinase (PI 3-kinase) are required for phagosome formation, but their role in maturation is unknown. Using chimeric fluorescent proteins encoding tandem FYVE domains, we found that phosphatidylinositol 3-phosphate (PI[3]P) accumulates greatly but transiently on the phagosomal membrane. Unlike the 3′-phosphoinositides generated by class I PI 3-kinases which are evident in the nascent phagosomal cup, PI(3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
509
3
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(549 citation statements)
references
References 29 publications
28
509
3
9
Order By: Relevance
“…Our data suggests VPS-34 is required for RAB-5 recruitment; in vitro studies have suggested an additional level of protein regulation, where Rab5 GTP promotes optimal VPS34 activity 67 . To further narrow down the mechanism of Vps34 function, we created transgenic nematodes expressing a YFP:: 2xFYVE fusion construct.…”
Section: Vps-34 Kinase Activity Is Regulated By Rab-5mentioning
confidence: 63%
“…Our data suggests VPS-34 is required for RAB-5 recruitment; in vitro studies have suggested an additional level of protein regulation, where Rab5 GTP promotes optimal VPS34 activity 67 . To further narrow down the mechanism of Vps34 function, we created transgenic nematodes expressing a YFP:: 2xFYVE fusion construct.…”
Section: Vps-34 Kinase Activity Is Regulated By Rab-5mentioning
confidence: 63%
“…If this is true, then the incoming endocytic vesicles should lack PtdIns(3)P and a key determinant of endosome identification would therefore be the activation of a PtdIns3K. Consistent with this proposal, PtdIns3KIII generates PtdIns(3)P on phagosomes only after they have budded off from the plasma membrane, and this is required for them to fuse with lysosomes (366).…”
Section: B Ptdins(3)p On Endosomesmentioning
confidence: 79%
“…Interestingly, following infection of DC, the Mtb strain lacking ESAT-6 and CFP-10 localized to LAMP-1 + phagolysomes (43), suggesting the pivotal role of these proteins in the inhibition of phagosome maturation. In addition to products of the ESX-1 gene, M. tuberculosis uses a range of lipids, such as lipoarabinomannan, and protein effectors to alter the phosphatidylinositol 3-phosphate signaling (44,45) involved in phagosome maturation. In particular, M. tuberculosis produces the phosphatase SapM, which specifically hydrolyses phosphatidylinositol 3-phosphate (35).…”
Section: Discussionmentioning
confidence: 99%